La diaspora : enjeux et débats / Frantz Jean Baptiste. - Jean-Baptiste, Frantz. (JEBCA Editions, 2013)
Essay discusses past and present Haitian diaspora and its relation with Haiti. Baptiste is former director of the magazine Diafrorama, radio speaker, and international relations consultant. His previous published works include "Haïti j'accuse: enquête inachevée" (2013).